Mitigation mechanism of zinc oxide nanoparticles on cadmium toxicity in tomato - Sun, Liangliang; Wang, Ruting; Ju, Qiong; Xing, Menglu; Li, Ruishan; Li, Weimin; Li, Wen; Wang, Wenying; Deng, Yanfang; Xu, Jin (Frontiers in Plant Science, 2023)
Cadmium (Cd) pollution seriously reduces the yield and quality of vegetables. Reducing Cd accumulation in vegetables is of great significance for improving food safety and sustainable agricultural development. A previous study demonstrated that the root application of zinc oxide nanoparticles (ZnO NPs) reduced Cd accumulation in rice. In this study, using tomato as the material, we analyzed the effect of foliar spraying with ZnO NPs on Cd tolerance and accumulation in tomato seedlings. Foliar spraying with ZnO NPs improves Cd tolerance by increasing photosynthesis efficiency and antioxidative capacity, while it reduces Cd accumulation but increases the accumulation of zinc, copper and manganese in the leaves of Cd-treated tomato seedlings. Subsequent metabonomic analysis showed that ZnO NP exposure alleviated the fluctuation of metabolic profiling in response to Cd stress, and it had a more prominent effect in leaves than in roots. Correlation analysis revealed that several differentially accumulated metabolites were positively or negatively correlated with the growth parameters and physiol-biochemical indexes. Taken together, this study revealed the response mechanism of the change in metabolic spectrum mediated by ZnO NPs to Cd tolerance in tomato seedlings and will enable us to better understand how ZnO NPs regulate plant growth and development and provide new insights into the use of ZnO NPs for improving growth and reducing Cd accumulation in vegetables.